The Effect of Service Quality, Ticket Prices and Ease of Transaction on Customer Satisfaction of Mass Rapid Transit Jakarta - Sihombing, Sarinah; Manik, Payaman; Ratu Anisya, Lutfia; Nurcahayati, Diana; Hidayat, Masjraul; Utami Yulihapsari, Ika (KnE Social Sciences, 2023)
Mass Rapid Transit (MRT) is an urban rail-based rapid transit system designed to reduce traffic congestion in Jakarta. Sales tactics and price determination can be used to implement good quality service. The relationship between price and quality is positive, which means the higher the price, the higher the quality. Moreover, transaction convenience is critical for MRT Jakarta passengers’ happiness. This research assessed the quality of service, ticket prices, and ease of transaction to assess the satisfaction of MRT Jakarta passengers. The independent variables were service quality, ticket price, and ease of transaction. The dependent variable was in the perusal of customer satisfaction. The population in this research was the average number of passengers of MRT Jakarta in June 2021, which was 18.936 people per day. The sample obtained from the population was 392 respondents selected by simple random sampling. Based on the results, the service quality variables had a significant value of 0.000, the ticket prices have a significant value of 0.000, and the ease of the transaction has a significant value of 0.026. It can be concluded that each variable influenced user satisfaction. Keywords: Mass Rapid Transit (MRT) , Service Quality , Ticket Prices, Ease of Transaction , Customer Satisfaction